(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
This research is motivated by government policies regarding the implementation of online attendance using face detector technology, in line with Presidential Regulation of the Republic of Indonesia Number 95 of 2018 concerning Electronic-Based Government Systems. The main objective of this study is to analyze the effectiveness of implementing online attendance (face detector) in improving employee discipline at the Petang District Office, Badung Regency, Bali, as well as to identify the inhibiting factors in its implementation. The research method employed is descriptive qualitative, using Duncan’s effectiveness theory, which includes the indicators of goal attainment, integration, and adaptation. The findings reveal that online attendance (face detector) has been implemented since 2018 as a follow-up to Government Regulation Number 53 of 2010 concerning Civil Servant Discipline. Socialization regarding its procedures has been carried out by the Badung Regency BKPSDM, enabling employees to understand its use. The implementation of online attendance has proven effective in enhancing employee discipline regarding arrival and departure times, thereby minimizing lateness and early departures. However, several obstacles remain, including technical errors in the device, unstable internet connectivity, and the absence of some employees during socialization sessions, which occasionally necessitates reverting to manual attendance. In conclusion, the implementation of online attendance (face detector) at the Petang District Office has been relatively effective in improving employee discipline, although certain technical and administrative challenges still need to be addressed to optimize the system’s performance.